Devising a method for calculating the structure of efficient cooling systems for thrust bearings and guide bearings in hydrogenerators - Tretiak, Oleksii; Kravchenko, Stanislav; Mykhailychenko, Oleksii; Nazarenko, Viacheslav; Smyk, Serhii; Vasyliev, Oleksandr; Arefieva, Mariia; Tretiak, Iryna; Serhiienko, Serhii; Selevko, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the thermal and hydraulic characteristics of the oil coolers in a thrust bearing and guide bearing cooling system of hydrogenerators. The study addresses the task to improve the efficiency of the cooling system of the supporting elements of hydrogenerators while maintaining mass and dimension indicators. The main problems in this case are the unbalanced flow of oil within the typical cooling system and different stiffness of the thrust bearing segment supports. The main result is the design of a cooling system structure that ensures effective heat removal from the oil. According to calculations, an oil cooler for a hydrogenerator with a capacity of 56 MW provides removal of 250 kW of losses with a heat transfer margin of 26.2%, for a hydrogenerator with a capacity of 96 MW – 150 kW and 31.8%, respectively. The results are explained by the use of new antifriction materials for supporting elements (fluoroplastic-4) and a higher strength group material for the thrust bearing disk. The designed structure of the cooling system enables operation with preservation of isotropy of cooling liquids and does not have "dead" zones of these liquids flow. A feature of the proposed method for calculating oil coolers is the addition to existing criterion equations of an experimental coefficient B, which takes into account the peculiarity of the geometry of the structure in addition to the nature of the oil flow and gas-dynamic parameters. The action of three-dimensional forces, temperatures, and pressures within the base metal and cooling liquids were comprehensively taken into account. The proposed structures of the thrust bearing and guide bearing, as well as their cooling systems, could be implemented in the design and modernization of medium and high-power hydrogenerators